Efficacy and safety of transarterial chemoembolization combining sorafenib with or without immune checkpoint inhibitors in previously treated patients with advanced hepatocellular carcinoma: A propensity score matching analysis - Yang, Xue-Gang; Sun, Yan-Yuan; Wang, Hai-Qing; Li, De-Shan; Xu, Guo-Hui; Huang, Xiao-Qi (Frontiers in Oncology, 2022)
Purpose To compare the efficacy and safety of transarterial chemoembolization (TACE) plus sorafenib and immune checkpoint inhibitors (T+S+ICIs) and TACE plus sorafenib (T+S) when treating patients with advanced hepatocellular carcinoma (HCC) who have previously received locoregional treatment. Materials and methods A retrospective analysis was performed on the patients with Barcelona Clinic Liver Cancer (BCLC) stage C HCC from May 2019 to December 2020. These patients were treated with locoregional therapy and showed radiographic progression after the treatment. Patients received either T+S+ICIs or T+S. The outcomes, including disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety, were compared. The propensity score matching (PSM) methodology was used to reduce the influence of confounding factors on the outcomes. Results Forty-three patients were included in the T+S group and 33 in the T+S+ICI group. After PSM (n = 29 in each group), patients who received T+S+ICIs had a higher DCR (82.8% vs. 58.6%, p = 0.043), longer median PFS (6.9 vs. 3.8 months, p = 0.003), and longer median OS (12.3 vs. 6.3 months, p = 0.008) than those who underwent T+S. Eastern Cooperative Oncology Group performance status was an independent predictor of PFS, and age was an independent predictor of OS. The incidence of treatment-related adverse events in T+S+ICIs was well controlled. Conclusions Compared with TACE combined with sorafenib, TACE combined with sorafenib plus ICIs is a potentially safe and effective treatment regimen for patients with advanced HCC who previously received locoregional treatment.